Impact of pulmonary yoga module on lung capacity of COVID-19 adult survivors - Adarsh Tomar; Sudhanshu Verma (BLDE University Journal of Health Sciences)
BACKGROUND: Although every organ has its own importance in the human body, the significance of the lungs is vital. Numerous complications can occur if lungs are compressed; cardiovascular and respiratory diseases are most common in such circumstances. Healthy lungs are associated with overall good health and strong immunity. During the COVID-19 pandemic, the lungs were the primary organs that failed and became the main cause of death. Yoga (YOG) provides a lot of solutions to get the lungs healthy. Nowadays, yogic practices are being used as a preventive measure against this deadly virus. There is a hypothesis that yoga improves lung capacity significantly, which is a front-line fighter against any pathogens or viruses that intrude inside the body. For a healthy and harmonious life, the functions of the lungs are supposed to work properly. Those with healthy lungs are less likely to get infected by viruses and tend to have better immunity which is the key factor for a healthy life. This study is going to delve into the efficacy of selective yogic practices on the lung capacity of a few common symptomatic coronavirus adult survivors as per addition and omission criteria. METHODOLOGY: Fifty subjects of 18–30 years age elected for the research work with the peer group range of 18–30 years (mean = 22.24), lung capacity, level of SpO2, and pulse rate of selected subjects were measured twice prior and end of the intervention for each participant. Expiratory peak flow measurements were taken of subjects to know the lung capacity through the expiratory peak flow meter. A pulse oximeter has been used to take data for SpO2 and pulse rate. Selected yogic practices were intervened for 2 months. The before-test and after-test data were taken, stored, and tabulated to find the efficacy of Yogic interventions. The simple random sampling technique applied for the selection procedure and expulsion standard is 10%. OUTCOME: After 8 weeks of yoga intervention (selected yogic practice) on day 60th, posttest data were taken and assessed on different significance levels (α). The mean peak flow was 291 and 353.80 before and after the intervention, respectively (P = 2.711). The mean SpO2 was 97.9 and 98.74 earlier and later in the intervention, respectively (P = 0.0134). The mean pulse rate was 88.00 and 84.90 prior and completion of the intervention, respectively (P = 0.2008). CONCLUSION: Indeed, as per the results and evidence, statistically significant changes in peak flow, level of SpO2, and pulse rate and selective yogic practices significantly affect the lung capacity, hence can be used for post-COVID-19 treatment as integrative, alternative, or complementary medicine.